Regiospecific Synthesis of N2-Aryl 1,2,3-Triazoles from 2,5-Disubstituted Tetrazoles via Photochemically Generated Nitrile Imine Intermediates - Stewart, Sam; Harris, Robert; Jamieson, Craig (Synlett, 2014)
The synthesis of N2-aryl 1,2,3-triazoles from 2,5-disubstituted tetrazoles was achieved under photochemical conditions. This simple and mild one-step reaction provides regiospecific access to 2,4,5-substituted 1,2,3-triazoles via a nitrile imine intermediate. Syntheses of alkyl and heterocylic derivatives were also investigated.
Keywords: photochemistry; regioselectivity; tetrazole; triazole; indazole